Analisis Efektivitas Penggunaan Ice Breaking Dalam Motivasi Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam Kelas XI Akuntansi dan Keuangan Lembaga (AKL ) SMK Negeri 01 Buay Madang - Marlina; Solehah, Nikmatus; Suhartono (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2024)
The research was carried out because researchers found interesting experiences during their educational internship at SMK Negeri 01 Buay Madang. These findings indicated that students experienced a lack of motivation in participating in learning activities, such as easily feeling bored, sleepy, and having difficulty maintaining focus. To increase students' learning motivation, namely by using Ice Breaking. The research aims: (1) How is Ice Breaking used in class XI AKL, (2) What are the supporting and inhibiting factors for using Ice Breaking, (3) What is the level of students' learning motivation. This research uses a qualitative approach with a qualitative descriptive type. Data was collected through interviews, observation and documentation. The research results showed that: (1) The use of Ice Breaking in class XI AKL occurred spontaneously during learning activities. (2) Supporting factors for using Ice Breaking include the attitude of students who are easy to direct, the enthusiasm and interest of students, the creativity of educators, and the availability of infrastructure. Factors inhibiting the use of Ice Breaking include student characteristics, educator limitations, and time constraints. (3) The interview results show that the use of Ice Breaking in class XI AKL has a positive impact on increasing students' learning motivation. By using Ice Breaking, the atmosphere and conditions in class XI AKL become more interesting, so that students are motivated and enthusiastic to take part in the learning process.